Can you afford to be ill : hospital service plan (London : The London Association for Hospital Services Limited)
1945 1945 1940s 15 pages : illustrations [Image] CAN YOU AFFORD TO BE ILL? HOSPITAL SERVICE PLAN FREEDOM FROM FEAR New Horizons 292/842/2/63